Uma arquitetura para sistemas supervisórios industriais e sua aplicação em processos de elevação artificial de petróleo - Souza, Rodrigo Barbosa de (2005)
The using of supervision systems has become more and more essential in accessing, managing and obtaining data of industrial processes, because of constant and frequent developments in industrial automation. These supervisory systems (SCADA) have been widely used in many industrial environments to store process data and to control the processes in accordance with some adopted strategy. The SCADA s control hardware is the set of equipments that execute this work. The SCADA s supervision software accesses process data through the control hardware and shows them to the users. Currently, many industrial systems adopt supervision softwares developed by the same manufacturer of the control hardware. Usually, these softwares cannot be used with other equipments made by distinct manufacturers. This work proposes an approach for developing supervisory systems able to access process information through different control hardwares. An architecture for supervisory systems is ﬁrst deﬁned, in order to guarantee efﬁciency in communication and data exchange. Then, the architecture is applied in a supervisory system to monitor oil wells that use distinct control hardwares. The implementation was modeled and veriﬁed by using the formal method of the Petri networks. Finally, experimental results are presented to demonstrate the applicability of the proposed solution